Oligocene Trace Fossil Geoconservation and Geoheritage: On the Mammals Tracks of the Luberon UNESCO Global Geopark - Pauline Coster; Stephane Legal (Geoconservation Research)
Trace fossils represent an important component of the Earth’s heritage that provide important keys for learning about the diversity and evolution of life and environments through time. They represent a rich and fragile geoheritage that requires special geoconservation measures.The Saignon tracksite, yielding thousands of tracks attributed to mammals, is located in the heart of the Luberon UNESCO Global Geopark. A conservation approach for this exceptional site is developed while promoting education, public awareness raising, geotourism and the sustainable development of Luberon through the valorization of its natural heritage.